Behavioral Responses of Nonsmokers to Environmental Tobacco Smoke Exposure - Irawati, Desrina Yusi; Sri Widari, Nyoman; Canariesa, Armadeo Ruben (Spektrum Industri, 2026)
Second-hand smoke (SHS) exposure remains a significant public health issue among Indonesian adolescents, particularly in areas where smoking is socially accepted and smoke-free regulations are weakly enforced. However, limited research explains the psychosocial mechanisms shaping protective intentions among adolescent passive smokers in non-metropolitan settings. This study examines the determinants of protective behavioral intention and actual SHS exposure by extending the Theory of Planned Behavior (TPB) with additional cognitive, emotional, and environmental constructs. By incorporating risk perception, emotional responses, psychological reactions, negative cognition, and environmental exposure, the study offers a context-sensitive behavioral framework for SHS in high-exposure environments. Data were collected through a survey of 140 adolescent non-smokers in Tanjung Selor, Indonesia, who were routinely exposed to cigarette smoke. The model was analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results show that emotional responses (Beta = 0.399, p < 0.001) and environmental exposure (Beta = 0.401, p < 0.001) significantly predict protective behavioral intention, whereas the classical TPB constructs show limited explanatory power. Risk perception exerts strong indirect effects through emotional responses (Beta = 0.678, p < 0.001) rather than directly influencing intention. Behavioral intention strongly predicts actual SHS exposure (Beta = 0.507, p < 0.001). These findings indicate that adolescents’ protective intentions are shaped more by affective and environmental factors than by rational evaluations alone. This study contributes to provide study extends TPB in SHS research and provides empirical guidance for emotion-driven and environment-focused tobacco control interventions in non-metropolitan regions.